Operations strategy : principles and practice - Van Mieghem, Jan A.; Allon, Gad (Belmont, MA : Van Mieghem, 2015)
This book explains the principles of operations strategy and describes how companies can apply these principles in practice to increase value.
Includes bibliographical references, index
osc 10/01/2019, ijb, 28/01/2019
Loans
Keywords: Strategy management; Business logistics; Production management